Insights on fluoroquinolones in cancer therapy: chemistry and recent developments. (September 2020) - Sharma, P.C.; Goyal, R.; Sharma, A.; Sharma, D.; Saini, N.; Rajak, H.; Sharma, S.; Thakur, V.K.
Abstract: Cancer is a very risky life-threatening disease having most formidable afflictions in the world. Several anticancer agents are commercially accessible, however, the emergence of acquired drug resistance along with extreme adverse effects of these clinically used anticancer medications are major barriers to the effective chemotherapy. Thus, it is recommended to rationally design the newer drugs with few side effects. Fluoroquinolone derivatives are of pivotal interest for researchers due to their admirable pharmacological and pharmacokinetic profiles. They exhibit several favourable characteristics including, higher bioavailability, excellent tissue penetration and relatively low prevalence of adverse and toxic effects. Due to their potential interventions in carcinogenesis and mutagenesis, the focus of the area of research is nowadays shifting towards anticancer aspects of these compounds. This review shows the recent advancements in the development of novel fluoroquinolones as potential anticancer and cytotoxic agents and structure-activity relationships along with the possible modes of action for further development and recent patents filed/granted related to anticancer activity from the last few years have also been tabulated. Also, this review is an attempt to focus on the various upcoming aspects of fluoroquinolones and provides a newer outlook on the possible roles of fluoroquinolones in the treatment of cancer. Scientific information identified in this paper is expected to be useful for aspiring researchers working on the anticancer activity of fluoroquinolones. Graphical abstract: Image 1 Highlights: Summarizes new developments in cancer therapy. Fluoroquinolones as innovative materials for cancer treatment. Summarizes the chemistry and recent advances on the usage of Fluoroquinolones.